Aplikasi Mitra Kerjasama Universitas Nasional dalam Bentuk MOA dan MOU Berbasis Web - Mikhael Kristian Mike; Gio Fandy H Nainggolan; Iskandar Fitri (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Cooperation is an effort made by several individuals and also groups to achieve an agreedgoal. The collaboration was given as a partnership between the National University and otherdomestic and foreign institutions and companies. With the collaboration program at NationalUniversity, student can carry out activities such as training, research, student exchangesduring partner relations. The process of this collaboration activity can be carried out inmanaging collaborative activities between other agencies, namely requiring a website to builda cooperation program that can express agreement from both parties. In this research, acooperation partner submission system was proposed for submitting a website using thewaterfall method. The application of the partner waterfall cooperation website which isimplemented on the website display page created with the help of web development software isusing Sublime text 3 and data management using Xampp. On the website page there areseveral criteria in the process of submitting cooperation at the National University whichforms the basic of agreement with the National University, namely in the form of an MoA(Memorandum of Agreement) memorandum of agreement and MoU (Memorandum ofUnderstanding) memorandum of agreement. The results of submissions from other agenciesgiven to the National University in the form of the cooperation proposal of each criterion. Theprocess of cooperation agreement with the waterfall method produces agencies and othercompanies that are entitled to the cooperation agreement.)